2014
DOI: 10.4067/s0718-27242014000200004
|View full text |Cite
|
Sign up to set email alerts
|

Does Service Innovation Matter in High-Tech Industry?

Abstract: Service innovation has been found to be a major driver of innovation performance in service contexts. But this issue raises questions concerning the extent to which the relationship between market orientation and innovation performance holds in the high-tech industry. Relatively little research has examined how market orientation contributes to innovation performance through service innovation. We here report an empirical study of 235 Taiwanese high-tech firms to examine the influence of market orientation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 94 publications
0
11
0
3
Order By: Relevance
“…Moreover, the findings of this study showed that organizational structure has a stronger effect on service innovativeness when inter functional coordination are high rather than low. Previous research also acknowledges the importance of inter-functional coordination for service innovation (Auh & Menguc, 2005;Wang, 2014) and more specifically the role of interfunctional coordination in the exploitation of market knowledge and thus developing customer focused innovative product and service ideas in restaurants (Altinay, 2014). This study went beyond the existing literature and showed that inter-functional coordination is essential for the effective utilization of the decentralized organizational structure leading to stronger service The results suggest that inter-functional coordination, and learning orientation each individually had positive and significant impact on service innovativeness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the findings of this study showed that organizational structure has a stronger effect on service innovativeness when inter functional coordination are high rather than low. Previous research also acknowledges the importance of inter-functional coordination for service innovation (Auh & Menguc, 2005;Wang, 2014) and more specifically the role of interfunctional coordination in the exploitation of market knowledge and thus developing customer focused innovative product and service ideas in restaurants (Altinay, 2014). This study went beyond the existing literature and showed that inter-functional coordination is essential for the effective utilization of the decentralized organizational structure leading to stronger service The results suggest that inter-functional coordination, and learning orientation each individually had positive and significant impact on service innovativeness.…”
Section: Discussionmentioning
confidence: 99%
“…From a practical standpoint, this implies that hotels can enhance service innovativeness by developing a forum for exchange and sharing new knowledge, experiences and ideas, resolution of problems, and innovative responsiveness as well as commitment to learning and shared values (Auh & Menguc, 2005). Thus, the fast dissemination and diffusion of new intelligence to related functions and coordinating the units' synergistic activities is required to foster service innovativeness within an organic structure (Wang, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…They complement goods and services sales (Kastalli and Van Looy, 2013), and the importance of organisational focus (i.e., product versus services) and design on profitability of additional services (Suarez et al, 2013;Eggert et al, 2014). There is also increased attention on differing ways products and services businesses' innovations occur (Mina et al, 2014), influences of service innovations on product innovation performance (Dachs et al, 2014;Wang, 2014), and export performance (Kelle, 2013;Lodefalk, 2014).…”
Section: Growing Research Concentrationsmentioning
confidence: 99%
“…Considering that co-creation is a basic feature of crowdsourcing (Cairns, 2013;Djelassi & Decoopman, 2013;Prahalad & Ramaswamy, 2004) and service innovation requires a high degree of integration between the organization and its customers, especially in knowledgebased sectors (Wang, 2014), this connection becomes a key point in the success of market orientation.…”
Section: Crowdsourcing and Market Orientationmentioning
confidence: 99%
“…In addition, firms can reduce costs by promoting selfservice areas via web and by transferring internal work processes to consumers (i.e., the concept known as outsourcing consumer), which is one of their basic motivations to establish a presence on the Internet (Kleemann, Voß, & Rieder, 2008). Therefore, crowdsourcing processes are advisable in terms of innovation and customer benefit (Magnusson, Matthing, & Kristensson, 2003;Wang, 2014).…”
Section: Introductionmentioning
confidence: 99%